1989
DOI: 10.1292/jvms1939.51.300
|View full text |Cite
|
Sign up to set email alerts
|

Protection against bovine rotaviruses in newborn calves by continuous feeding of immune colostrum.

Abstract: Three pregnant cows were inoculated intramuscularly with inactivated vaccine to bovine rotavirus (BRV) serotype 1 (BRV-1) and serotype 2 (BRV-2). Serum neutralizing antibody (NA) titers against both serotypes increased significantly after immunization. NA titers of colostrum obtained from immunized cows against BRV-1 and BRV-2 were 29286 and 38109, respectively, which were significantly higher than those from non-immunized control cows. Nine and 6 colostrum deprived calves were orally challenged with BRV-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
11
1
4
Order By: Relevance
“…These colostrum antibody titers may be protective against BRV and K99 E. coli associated with calf diarrhea, as previous studies have described the protective antibody titers against experimental BRV and K99 E. coli challenge [1,7,8,10,14,18]. However, it was unclear that this vaccine was effective in the prevention of outbreaks of calf diarrhea in the field.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…These colostrum antibody titers may be protective against BRV and K99 E. coli associated with calf diarrhea, as previous studies have described the protective antibody titers against experimental BRV and K99 E. coli challenge [1,7,8,10,14,18]. However, it was unclear that this vaccine was effective in the prevention of outbreaks of calf diarrhea in the field.…”
mentioning
confidence: 87%
“…During the first few weeks of life, calves acquire maternal antibodies from colostrum and milk, which can exert a local protective effect against enteropathogens in the gut as passive immunity. Previous studies demonstrated that continuous feeding of colostrum from immunized cows prevented severe diarrhea and death in calves [1,10,12,14,18]. In North America and Europe, various maternal vaccines against calf diarrhea to enhance antibody titers in the colostrum and milk of cows have been developed [7,11,14,17,20].…”
mentioning
confidence: 99%
“…Por outro lado, tem sido atribuído papel de proteção local aos anticorpos existentes no colostro fornecido suplementarmente aos bezerros, os quais protegeriam a mucosa intestinal do ataque patogênico pela aderência a mesma, levando a menores incidências de diarréia (SNODGRASS et al, 1980;SAIF et al, 1983;SAIF & SMITH, 1985;BELLINZONI et al, 1989;CASTRUCCI et al, 1989;TSUNEMITSU et al, 1989).…”
Section: Introductionunclassified
“…Studies on passive immunity have demonstrated that continuous feeding of colostrum or milk containing rotavirus-specific antibodies prevented the BRV disease in calves, which is called lactogenic immunity [8,11,12,14,16,17]. Additionally, circulating maternal BRV-specific antibodies in newborn calves appeared in the gastrointestinal tract, and these antibodies could prevent infection and diarrhea after BRV challenge [1,2].…”
mentioning
confidence: 99%